Application of poly(ethylene terephthalate)-graft-polystyrene membranes in pervaporation - Khayet, M.; Nasef, M. M.; Mengual, J. I. (Elsevier Science B.V., 2006)

(untitled)
Gamma radiation-induced grafting of styrene (ST) onto poly(ethylene terephthalate) (PET) films was used to prepare poly(ethylene terephtalate)/polystyrene (PET-g-PST) membranes having various degrees of grafting. Various characterization techniques were used to study both surface and bulk properties of the un-grafted PET and the grafted PET-g-PST membranes. The pervaporation performance of the membranes was investigated using a 50:50% v/v methanol/toluene mixture at 25Â°C. The effects of the degree of grafting on the sorption behaviour, the pervaporation flux and the permeation selectivity of the membranes were studied. The pervaporation performance of the membranes has been explained using the solubility parameter approach. All the investigated membranes were found to be toluene selective. However, the grafted PET-g-PST membranes exhibit better pervaporation performance than the un-grafted PET membrane as indicated by their high toluene selectivity. Among all PET-g-PST membranes, 35% grafted membrane possesses the most appealing pervaporation properties.